Building Communities : Social Networking For Academic Libraries. - Garofalo, Denise; ScienceDirect eBooks (Chandos Publishing, 2013)
A robust social media campaign can provide academic libraries with a means to showcase library resources, highlight content and events, and attract students to sample what the library has to offer. "Building Communities" is a handbook to implement social media technologies for academic libraries. It is a guide to planning and implementing a successful social media campaign and evaluating its impact. This title covers the beginning of social networking in the academic context, how to implement use of social media technologies, and evaluating their use. The final section considers the future and asks: "Whats next?"
1. The whats and whys of social networking for academic libraries -- 2. How to approach the implementation of social media technologies -- 3. Case studies of academic libraries and social media networking -- 4. First steps -- 5. Make the connection : posting on social media -- 6. Evaluating the impact of social media in academic libraries -- 7. Closing thoughts.
Includes bibliographical references and index.
Print version record.
Safari Books Online
Elsevier
Keywords: Online social networks -- Library applications; Academic libraries -- Information technology; Social media; Libraries and community; Electronic books